Returning to thinking theologically – breaking down the borders between east and west: an interdisciplinary exercise - Jasper, David (Creativity Studies, 2013)
This essay explores the developments in Christian theology which are taking place in the encounter with the ancient Chinese classic texts. These are being revisited in Chinese universities where scholars from the West and the East are seeking a common religious language through what has been termed a form of “scriptural reasoning”. Links are especially made through the work of radical European thinkers of the present time such as Slavoj Žižek and Gianni Vattimo.Grįžimas prie teologinio mąstymo, griaunant sienas tarp rytų ir vakarų: interdisciplininė treniruotėSantrauka. Šiame straipsnyje tyrinėjama krikščioniškosios teologijos raida sandūroje su senovės kinų klasikų tekstais. Šie tekstai buvo peržiūrėti Kinijos universitetuose, kur mokslininkai iš Vakarų ir Rytų ieškojo bendrosios religijos kalbos, apibūdinančios „biblinį mąstymą“. Sąsajos yra sudarytos ypač per dabartinės Europos radikaliųjų mąstytojų, tokių kaip Slavojus Žižekas ir Gianni Vattimo, darbus.Reikšminiai žodžiai: interdiscipliniškumas, misticizmas, teologija, besąlygiškumas, wu wei.First published online: 31 Dec 2013